Effectiveness of Trans Theoretical Model on diabetes self-management and HbA1C level in Men and Women with type 2 diabetes - Moeini, Fatemeh; Mohammadi Shirmahaleh, Fatemeh; Tajeri, Biuok; Shirafkan, Ali; Jianagheri, Masoumeh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of Trans Theoretical Model on diabetes self-management and HbA1C level in patients with type 2 diabetes. Methods: The method of this study was applied and quasi-experimental designs of pre-test-post-test and follow-up with the control group. The statistical population of the study consisted of 25-55 years old diabetic patients referred to one of the health centers in Ghaemshahr in 2020, among which 30 people were selected by purposeful sampling method and were assigned to two groups of Trans Theoretical Model (n=20) and control group (n=20). Data were obtained through Tobert and Glasgow Diabetes Self-Management Questionnaire (2002) and glycosylated hemoglobin test (HbA1c). For data analysis, repeatedly measuring variance analysis (MIX) and SPSS-22 software were used. Results: The results showed that cognitive-behavioral group had a significant effect on diabetes self-management (F=38.01, p